“And the rifle, who do you sell to?”: The different meanings of corruption for candidates who want to join the military police force in Rio de Janeiro - Rodrigues, Eduardo de Oliveira (Revista de Antropologia, 2022)
The structure of different illegal markets requires the participation of law enforcement agents in their operation. In Brazil, this is part of what is known as “police corruption”. Many works on this topic consider corruption as a deviation from established norms, which is explained, in relation to the police, due to problems related to the training received by the recruits at the academy and, mainly, to the police subculture learned on the streets. The present article, however, suggests a different approach to the problem. It is based on an ethnographic research with candidates for the military police career prior to any formal contact with the force. Taken as a result of “social classification” processes, corruption is a dynamic category nurtured by “situational moralities” that permit the agency of social actors. What are the different meanings of corruption for candidates who want to join the military police in Rio de Janeiro?